Contextuality, interculturality and decolonisation as schemes of power relations - Igboin, Benson Ohihon (HTS teologiese studies, 2023)
Western imperialism and colonialism have tremendously affected the epistemological conception of Africa and Africans. In the same vein, early missionaries did not countenance the cosmologies and lived experiences of the Africans in their interpretation and application of the Bible. On the contrary, they imposed Western epistemologies and theological images on Africa. Although much work has been carried out in these areas, little attention has been devoted to how contextuality, interculturality and decolonisation are exercised in power struggles: the power to define what counts for Africa and Africans as they daily deploy the resources of the Bible. The author argues that contextuality, interculturality and decolonisation are schemes of power relations on the one hand and of owning the Bible on the other, rather than mere methods of biblical hermeneutics in Africa. As schemes of power, they reject imperialist agenda of unequal barter of cultural exchange claimed as civilising the African. Presenting contextuality as a finished product is a violation of the rights of Africans to productively apply the Bible as a text seeking understanding in a different clime from the West; it is also a denial of the reality of interculturality, and thus it ignites the need for decolonisation. By utilising conceptual analysis as a framework, it is argued that these schemes are beyond hermeneutical methods but have the power to resist the suffusing influence of Western theological suffocation in Africa.Contribution: This study argues that contextuality, interculturality and decolonisation are not mere hermeneutical methods for studying the Bible in context; they are instruments of struggle to liberate it from Western epistemological stranglehold.